Empirical assessment of the strategic adaptation of agro-industrial regions to external pressure - Elshin Leonid; Mingulov Almaz; Galeeva Gulnaz (E3S Web of Conferences)
The potential for sustainable development in agrarian-specialized regions, which contribute to national food security and shape key aspects of quality of life, is particularly significant amid the intensifying sanctions confrontation. This study addresses these critical issues. Drawing on a synthesis of foreign and Russian practices, it develops a conceptual framework and tools for empirically assessing the sustainability of agro-industrial regional economic systems. The author's approach is built on a three-dimensional model that evaluates processes through three key components: readiness for systemic transformations, and a combined export and import dependence indicator that measures regional vulnerability to shifts in foreign economic relations. The methodological foundation of the study includes econometric analysis, data aggregation and decomposition, and descriptive analysis. The study culminates in an assessment of the shock resilience of agrarian regions in the Volga Federal District, providing a basis for formulating policy recommendations to support regional development amid systemic transformations.